Pengaruh Pendapatan Asli Daerah, Dana Perimbangan dan Pengeluaran Pendidikan terhadap Indeks Pembangunan Manusia di Kabupaten Tulungagung - Christian Thomas Soenarko; Ignatia Martha Hendrati (Journal of Economics Development Issues, 2023)
The purpose of this study is to prove whether or not there is an influence between the independent variables (PAD), Balance Fund, and Education Expenditure) on the dependent variable (IPM) in Tulungagung Regency in 2007 - 2021. The source of the data for this research is the Directorate General of Fiscal Balance. Tulungagung Regency BPS, Tulungagung Regency Regional Development Planning Agency and Tulungagung Regency BPKAD. Multiple linear regression is an analysis that researchers use to see whether or not there is an effect. The results of the research prove that the variable of the Balanced Fund and Education Expenditure has an effect on the growth of HDI. In contrast to the PAD variable, it does not affect the HDI in Tulungagung Regency.